A transparent polyimide structure and preparation method thereof

By using alternating copolymerized ester cyclic dianhydride and fluorodiamine in transparent polyimide film, combined with the reaction of blocking agent, the problems of yellowing of the film and isomer generation are solved, and high transparency and Heat resistance, suitable for flexible displays and wearable devices.

CN116253879BActive Publication Date: 2025-02-07TAIHU HUAQIANG TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202211601310.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-13
Publication Date
2025-02-07
Estimated Expiration
2042-12-13

AI Technical Summary

Technical Problem

The existing transparent polyimide films have yellow or brown colors due to charge transfer complexes in the molecular structure, making them difficult to apply to the display field. They are prone to isomers during their synthesis, affecting the degree of polymerization and mechanical properties.

Method used

Two ester cyclic dianhydrides that are not easy to form isomers are used to alternately copolymerize with fluorine-containing diamines. The charge transfer is inhibited through structural design, and a highly transparent polyimide is formed, and the heat resistance is improved through the reaction of the capping agent. Bending resistance.

Benefits of technology

The high transparency, heat resistance and bending resistance of polyimide films are achieved, while reducing production costs, and are suitable for covering materials for flexible displays and wearable devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116253879B_ABST
    Figure CN116253879B_ABST
Patent Text Reader

Abstract

The present invention relates to a structure of a transparent polyimide and a preparation method thereof. The transparent polyimide is obtained by alternately copolymerizing two alicyclic dianhydrides and a fluorine-containing diamine and end-capping with a monoacid anhydride containing an unsaturated double bond. Cross-linking can occur during film formation. The obtained transparent film has the characteristics of good heat resistance, good dimensional stability and high light transmittance at 400 nm, and the cross-linked structure has the characteristic of being resistant to bending, thereby meeting the needs of future flexible display or flexible wearable devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of polymer materials for flexible displays and flexible wearable devices, and specifically relates to a transparent polyimide film that can be used for flexible displays and flexible wearable devices, and a method for preparing the film. Background Art

[0002] In recent years, with the continuous upgrading of electronic terminal mobile devices, more and more devices are developing in the direction of being thin, light and short. Among them, the display screens of mobile phones, computers, and tablets have completed a full set of industrial upgrades from inorganic light-emitting technology to organic light-emitting diode (OLED) technology. The future trend brought by organic light-emitting bodies is the continuous thinning and flexibility of screens, and even foldability. This trend has set off the reserve and competition of industry technology. In addition, the significance of the thinness and shortness of electronic mobile terminals is that people can carry or stick the terminals on their bodies without interfering with daily activities. The needs of the electronics industry force the development of materials. As inorganic materials for display cover plates of mobile phones, tablets and watches, glass and sapphire may be replaced by flexible transparent polyimide.

[0003] Electronic grade polyimide film has been widely used as the main insulating material of flexible copper clad laminate for more than ten years due to its good temperature resistance, mechanical properties, high and low temperature dimensional stability, and excellent dielectric and electrical properties. However, due to the special molecular structure of polyimide, there are strong interactions within and between molecules to form charge transfer complexes. This strong interaction causes the usual polyimide film to have golden yellow, yellow brown or even dark brown color, so that polyimide materials without structural design are difficult to be used in display cover plates of electronic devices. Therefore, the preparation of transparent polyimide that meets the required characteristics of cover plate materials has become the primary requirement of the display industry in the field of polymer materials.

[0004] The structurally designed polyimide film breaks the charge transfer complex in its molecular structure and can achieve transparency in the visible light range. The structural design can be done by the following four methods: 1. Introducing fluorine atoms into the raw material dianhydride or diamine; 2. Using ester ring (non-aromatic ring) dianhydride or diamine; 3. Introducing bulky substituents; 4. Using dianhydride or diamine with a twisted non-coplanar structure, among which the first and second methods are more commonly used.

[0005] The earliest industrialized transparent polyimide was a polymer of hexafluorodianhydride (6FDA) and 4,4'-diamino-2,2'-bistrifluoromethylbiphenyl (TFMB), which was used in the field of optical waveguides; however, the cost of this structure was relatively high, and due to the presence of a large number of benzene rings, it could not be used in the display field. Compared with fully aromatic polymers, polymers with ester ring main chain structures have significantly lower heat resistance, relatively lower Tg, and higher thermal decomposition temperature. As for the research on ester ring structure, as early as 1993 and 1994, the Japanese scholar Toshikazu Kurosaki published a series of articles in the magazine "Macromolecules" on the synthesis of special rigid ester ring dianhydride monomers, thereby synthesizing high-temperature resistant transparent polyimide. The glass transition of the optimal structure can be increased to 400°C, and the 5% weight loss temperature in a nitrogen atmosphere is increased to 520°C. Mitsubishi Gas Chemical Co., Ltd. of Japan was one of the first companies to industrialize transparent polyimide films. Its patent application number CN201880021617.8 disclosed a transparent polyimide structure in which hydrogenated pyromellitic anhydride was used as an ester cyclic dianhydride and two fluorinated diamines were copolymerized. The structure involved in this patent has a transmittance of more than 90% and a glass transition temperature of more than 380°C. Mitsubishi Gas' patent with application number CN202080011449.1, Tongji University's patent with application number CN201810397632.4, and Sinopec's patent with application number CN201811235126.1 all involve the use of alicyclic dianhydrides to prepare transparent polyimides, and all involve the structure of cyclobutane tetracarboxylic dianhydride. The transparent polyimide prepared by the alicyclic dianhydride not only has high light transmittance, but also has excellent heat resistance; however, the synthesis of alicyclic dianhydrides is quite difficult, and is often accompanied by the formation of isomers. The isomers of the above-mentioned ester ring dianhydrides have been reported in detail in the literature. The presence of isomers brings many adverse effects to polymerization, and even the degree of polymerization does not meet the requirements, and it is impossible to prepare a film with mechanical strength. In addition, the isomer separation technology is also one of the difficulties, and it is difficult to break through in the short term and reach the industrial level. Summary of the invention

[0006] In order to solve the above problems, the present invention aims at the existing technical difficulties in transparent polyimide, adopts two cycloaliphatic dianhydrides that are not easy to generate isomers during the synthesis process, and alternately copolymerizes them with fluorinated diamines to provide a new type of transparent polyimide. Without affecting the transparency, the heat resistance and bending resistance are greatly improved, thereby reducing the cost.

[0007] In this regard, firstly, in a first aspect of the present invention, a transparent polyimide is provided, wherein the main chain structure of the polyimide comprises two alicyclic dianhydrides at the same time, and the two alicyclic dianhydrides are arranged alternately on the main chain structure; wherein the structures of the two alicyclic dianhydrides are respectively as follows:

[0008]

[0009] As mentioned above, the reason why polyimide appears yellow, brown or brown is that the strong interaction between or within the polyimide molecules forms a charge transfer complex. In order to obtain transparent polyimide, special diamines or dianhydrides are usually used to inhibit charge transfer. The most common way is to introduce an aliphatic skeleton or a fluorine-containing group, but the dianhydride or diamine of the aliphatic skeleton has the problem of poor heat resistance, so it is preferred to use a fluorine-containing diamine or dianhydride.

[0010] Therefore, preferably, the transparent polyimide of the present invention uses a diamine containing a fluorine group for polymerization. Further, the diamine for polymerization is any one of the following two types:

[0011]

[0012] In a preferred embodiment, the transparent polyimide further comprises groups obtained by using an end-capping agent at both ends of the molecule.

[0013] Preferably, the end-capping agent is selected from monoanhydrides containing unsaturated bonds, preferably phthalic anhydride, glutaric anhydride, maleic anhydride Or any capping agent available in the art.

[0014] In a further preferred embodiment, the present invention provides a transparent polyimide, the main chain structure of which is shown in the following formula:

[0015]

[0016] Wherein, the value of N is an integer between 15-200, preferably an integer between 20-100; further, preferably an integer between 50-100;

[0017] Further, each R1 is independently selected from a group obtained by polymerization of a fluorine-containing diamine and an alicyclic dianhydride; preferably, each R1 is independently selected from any one of the following structures:

[0018]

[0019] Wherein, R2 is a functional group obtained by reacting a capping agent, and the capping agent is selected from a monoanhydride containing an unsaturated bond, such as phthalic anhydride, glutaric anhydride, etc.; preferably, each R2 is independently selected from a group obtained by one or more capping agents in the following group:

[0020]

[0021] On the other hand, the present invention also provides a method for preparing the transparent polyimide:

[0022] 1. Polymerizing the first dianhydride and the fluorine-containing diamine to obtain a polyamic acid intermediate A;

[0023] 2. Polymerize the polyamic acid intermediate A and the second dianhydride, add a capping agent to react and obtain polyimide;

[0024] 3. The polyimide is precipitated, washed and dried to obtain the transparent polyimide of the present invention.

[0025] In a specific embodiment, the first and second dianhydrides are selected from butane-1,2,3,4-tetracarboxylic dianhydride and 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic anhydride, or 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic anhydride and butane-1,2,3,4-tetracarboxylic dianhydride.

[0026] Preferably, the specific steps of the method for preparing the transparent polyimide of the present invention are:

[0027] 1. Add fluorinated diamine to the solvent, dissolve it, add butane-1,2,3,4-tetracarboxylic dianhydride, stir in an ice bath to react, then heat to room temperature, add dehydrating agent and catalyst, stir at room temperature to react, heat and stir for 2 hours, stop the reaction, cool down the reaction solution to precipitate, wash with methanol, and dry to obtain intermediate A for use.

[0028] 2. Add intermediate A to the solvent to dissolve, add another dianhydride, i.e., 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic anhydride, stir in an ice bath to react, warm to room temperature, observe the viscosity, stop adding dianhydride, then add end-capping agent, stir at room temperature to react, add dehydrating agent and catalyst, stir at room temperature, heat and stir. The reaction solution is precipitated into methanol, washed repeatedly, and vacuum dried to obtain the transparent polyimide of the present invention.

[0029] Specifically, the fluorinated diamine described above in the present invention may be one or more, preferably one or two selected from the following:

[0030] Specifically, the end-capping agent is a monoanhydride containing an unsaturated bond, such as phthalic anhydride, glutaric anhydride, etc.; preferably, it is one or more end-capping agents in the following group:

[0031]

[0032] Specifically, the dehydrating agent is selected from acetic anhydride, and the catalyst is selected from triethylamine, dimethylamine, methylamine, diisopropylethylamine, etc., preferably triethylamine.

[0033] In the step 1, the dehydrating agent and the catalyst mixture are measured in moles at twice the amount of butane-1,2,3,4-tetracarboxylic dianhydride; in the step 2, the end-capping agent is measured in moles at twice the difference between the molar numbers of the intermediate A and 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic anhydride.

[0034] Specifically, in step 1, the reaction is stirred in an ice bath for 6-12 hours, preferably 8-10 hours, and the reaction is stirred at room temperature for 4-10 hours, preferably 4-8 hours. The heating temperature is preferably 30-80°C, more preferably 50°C, and the heating and stirring reaction time is preferably 1-3 hours, more preferably 2 hours.

[0035] Specifically, in step 2, the reaction is stirred in an ice bath for 10-12 hours, the first stirring reaction is carried out at room temperature for 4-6 hours, and the second stirring reaction is carried out at room temperature for 12 hours; the heating temperature is preferably 30-80°C, more preferably 50°C, and the heating stirring reaction time is preferably 1-3 hours, more preferably 2 hours.

[0036] Specifically, the solvent is preferably an aprotic polar solvent, preferably N,N-dimethylacetamide, acetonitrile di-N,N-dimethylformamide, dimethyl sulfoxide, hexamethylphosphoric triamide, and more preferably N,N-dimethylacetamide.

[0037] Preferably, the reaction is carried out under a H2O atmosphere.

[0038] Preferably, the specific synthesis method of the transparent polyimide of the present invention is as follows:

[0039] 1. In a dry three-necked flask filled with nitrogen, add a certain amount of any fluorine-containing diamine, then add N,N-dimethylacetamide solvent, and after it is completely dissolved, add butane-1,2,3,4-tetracarboxylic dianhydride in an amount of half the molar number of the diamine, stir in an ice bath for 6-12 hours, then warm to room temperature, gradually dropwise add a mixture of a dehydrating agent and a catalyst in an amount of twice the molar number of the diamine, first stir at room temperature for 4-8 hours; then heat to 50°C, stir for 2 hours, stop the reaction, cool down, precipitate the reaction solution into excess methanol, wash repeatedly with methanol, and vacuum dry the intermediate product A to obtain a white powder for standby use.

[0040] 2. Add a certain molar amount of intermediate product A to a dry three-necked flask filled with nitrogen, add solvent N-methylpyrrolidone, and after it is completely dissolved, gradually add another dianhydride 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic anhydride in batches, stir under ice bath for 10-12 hours, and observe the viscosity after returning to room temperature. If the viscosity reaches 40000-60000 mPa·s, stop adding 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic anhydride. -3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic anhydride, record the amount of dianhydride added, calculate by mole, then add a capping agent twice the molar difference between the intermediate product A and 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic anhydride, stir at room temperature for 4-6 hours, then add a mixture of a dehydrating agent and a catalyst 4-6 times the molar number of the intermediate product A, stir at room temperature for 12 hours, heat to 50°C and react for 2 hours. End the reaction, precipitate the viscous reaction liquid into a large amount of methanol, wash repeatedly, and vacuum dry to obtain the transparent polyimide of the present invention.

[0041] On the other hand, the present invention further provides a transparent polyimide film, which comprises the transparent polyimide described above in the present invention; in a preferred embodiment, the polyimide film is obtained by dissolving and diluting the transparent polyimide described in the present invention and then coating it into a film.

[0042] Preferably, the transmittance (%) of the transparent polyimide film at a wavelength of 400 nm is 80% or more, more preferably 85% or more, more preferably 88% or more, and even more preferably 90% or more.

[0043] In another aspect of the present invention, the transparent polyimide film has a thickness of 10 μm-200 μm, preferably 10-100 μm, more preferably 10-50 μm, even more preferably 20-40 μm, and most preferably 25 μm.

[0044] In another aspect of the present invention, the thermal expansion coefficient of the transparent polyimide film is 30 ppm / K or less, more preferably 25 ppm / K or less, and even more preferably 20 ppm / K or less.

[0045] On the other hand, the present invention also provides a method for preparing the transparent polyimide film, which is characterized by comprising the steps of dissolving the transparent polyimide and coating the transparent polyimide on a carrier to form a film.

[0046] On the other hand, the present invention also provides a flexible display device covering substrate, which comprises the transparent polyimide described above in the present invention, or the transparent polyamide film described above in the present invention; preferably, the flexible display device covering substrate also includes a device protection layer, such as a hydrophobic hard coating.

[0047] In another aspect, the present invention further provides an optical material, which comprises the transparent polyimide described above in the present invention, or the transparent polyamide film described above in the present invention, or the flexible display device cover substrate described above in the present invention.

[0048] On the other hand, the present invention also provides an image display device, which comprises the transparent polyimide described above in the present invention, or the transparent polyamide film described above in the present invention, or the flexible display device cover substrate described above in the present invention, or the optical material described above in the present invention.

[0049] In another aspect, the present invention further provides an electronic device or device, which comprises the transparent polyimide described above in the present invention, or the transparent polyamide film described above in the present invention, or the optical material described above in the present invention.

[0050] In another aspect of the present invention, it also relates to the use of the transparent polyimide described above in the present invention in preparing a transparent polyimide film or a cover substrate of a display device.

[0051] As used herein, the term "comprising" and its variations also include different and varied terms, such as but not limited to "consisting essentially of" or "consisting of." When necessary, the numerical ranges provided herein also include sub-ranges therebetween.

[0052] The film made of the transparent polyimide of the present invention can be applied to various scenarios, such as display substrates, electronic printed products, optical materials, image display devices, electronic equipment or devices, and can also be used as a substitute for glass or other transparent materials.

[0053] Preferably, the display substrate is selected from a flexible display screen substrate, a conductive film substrate, etc.; the image display device is selected from a flexible display screen, a liquid crystal display screen, an electronic newspaper, etc.; the electronic device / device is selected from, for example, an electronic touch screen, a solar cell panel, etc. About. Regarding optical materials, for example, there are optical films, etc.

[0054] As used herein, without affecting the beneficial effects of the transparent polyimide of the present invention, the transparent polyimide of the present invention can be mixed with a conductive material according to the needs of the application scenario, so that the polyimide film has conductivity.

[0055] As used herein, the transparent polyimide film of the present invention further includes a hue adjusting material, such as a dye, a fluorescent material or a pigment, according to the application scenario.

[0056] The beneficial effects of the present invention are as follows: the present invention adopts two cycloaliphatic dianhydrides which are not easy to generate isomers in the synthesis process, and alternately copolymerizes with fluorinated diamines, so that the structure is highly ordered, and the mechanical properties can be improved after film formation. At the same time, cycloaliphatic monoanhydrides with double bonds are used for end-capping. During the heating process of film formation, the double bonds of the transparent polyimide are opened by heat, and cross-linking occurs, which not only does not affect the transparency, but also greatly improves the heat resistance and bending resistance.

[0057] To clearly illustrate the technical solution of the embodiment of the present invention, the steps involved in the embodiment and the corresponding drawings are introduced and explained below. Obviously, the drawings or embodiments described below are only examples of a part of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 : Infrared absorption spectra of transparent polyimide of Example 1-4;

[0059] Figure 2 : UV transmission spectrum of transparent polyimide of Example 1-4;

[0060] Figure 3 : TMA spectra of the transparent polyimide of Example 1 and Example 4;

[0061] Figure 4 : TMA spectra of the transparent polyimide of Example 2 and Example 3;

[0062] Figure 5 : Thermogravimetric spectra of transparent polyimide of Example 1-4 and Comparative Example 2;

[0063] Figure 6 : The transparent polyimide structural formula of the present invention. DETAILED DESCRIPTION

[0064] The present invention will be better understood with reference to the above-mentioned drawings and the following examples. However, it should be understood that the drawings and examples of the present disclosure are only for illustrative purposes and represent only some specific embodiments of the present invention, and are not intended to limit the scope of protection of the present disclosure, which can be implemented in various forms.

[0065] Embodiment 1:

[0066] In a dry three-necked flask vented with nitrogen, add 3.2 g (10 mmol) of diamine 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, then add 60 ml of N,N-dimethylacetamide solvent, after complete dissolution, add 0.99 g (5 mmol) of butane-1,2,3,4-tetracarboxylic dianhydride, stir in an ice bath for 8 hours, then warm to room temperature, gradually add dropwise a mixture of 2.04 g (20 mmol) of acetic anhydride and 2.02 g (20 mmol) of triethylamine, first stir at room temperature for 4 hours; then heat to 50°C, stir for 2 hours, stop the reaction, cool down, precipitate the reaction solution into a large excess of methanol, wash repeatedly with methanol to obtain intermediate product A1, vacuum dry to obtain a white powder for standby use.

[0067] 8.38 g (10 mmol) of the intermediate product A1 was added to a three-necked flask that was dried and purged with nitrogen, and 48 ml of the solvent N-methylpyrrolidone was added. After complete dissolution, another dianhydride 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic anhydride was gradually added in batches. The mixture was stirred for 10 hours under an ice bath. After returning to room temperature, the viscosity was observed. When the viscosity reached 49380 mPa·s, the addition of 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic anhydride was stopped. Dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic anhydride, at this time, the amount of dianhydride added is 2.94g (9.8mmol), followed by adding 0.0392g (0.4mmol) of end-capping agent maleic anhydride, stirring at room temperature for 4 hours, then adding a mixture of 4.08g (40mmol) of acetic anhydride and 4.04g (40mmol) of triethylamine, stirring at room temperature for 12 hours, and then heating to 50°C for 2 hours. After the reaction is terminated, the viscous reaction liquid is precipitated into a large amount of methanol, repeatedly washed, and vacuum dried to obtain a transparent polyimide No. 1 sample, which is dissolved and scraped into a film with a thickness of 25μm for standby testing.

[0068] Embodiment 2:

[0069] In a dry three-necked flask vented with nitrogen, add 3.96g (10mmol) of diamine 1,4-bis(2-trifluoromethyl-4-aminophenyl)benzene, then add 60ml of N,N-dimethylacetamide solvent, after complete dissolution, add 0.99g (5mmol) of butane-1,2,3,4-tetracarboxylic dianhydride, after stirring in an ice bath for 10 hours, then warm to room temperature, gradually add dropwise a mixture of 2.04g (20mmol) of acetic anhydride and 2.02g (20mmol) of triethylamine, first stir at room temperature for 6 hours; then heat to 50°C, stir for 2 hours, stop the reaction, cool the reaction solution, precipitate it into a large excess of methanol, wash it repeatedly with methanol, and obtain intermediate product A2, vacuum dry it to obtain a white powder for standby use.

[0070] 9.90 g (10 mmol) of the intermediate product A2 was added to a dry three-necked flask filled with nitrogen, and 55 ml of the solvent N-methylpyrrolidone was added. After complete dissolution, another dianhydride 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic anhydride was gradually added in batches. The mixture was stirred for 12 hours under an ice bath. After returning to room temperature, the viscosity was observed. When the viscosity reached 57690 mPa·s, the addition of 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic anhydride was stopped. Dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic anhydride, at this time, the amount of dianhydride added is 2.97g (9.9mmol), followed by 0.0304g (0.2mmol) of end-capping agent tetrahydrophthalic anhydride, stirring at room temperature for 6 hours, then adding a mixture of 4.08g (40mmol) of acetic anhydride and 4.04g (40mmol) of triethylamine, stirring at room temperature for 12 hours, and then heating to 50°C for 2 hours. After the reaction is terminated, the viscous reaction liquid is precipitated into a large amount of methanol, repeatedly washed, and vacuum dried to obtain a transparent polyimide No. 2 sample, which is dissolved and scraped into a 25μm thick film for standby testing.

[0071] Embodiment 3:

[0072] In a dry three-necked flask vented with nitrogen, add 3.96g (10mmol) of diamine 1,4-bis(2-trifluoromethyl-4-aminophenyl)benzene, then add 60ml of N,N-dimethylacetamide solvent, after complete dissolution, add 0.99g (5mmol) of butane-1,2,3,4-tetracarboxylic dianhydride, after stirring in an ice bath for 10 hours, then warm to room temperature, gradually add dropwise a mixture of 2.04g (20mmol) of acetic anhydride and 2.02g (20mmol) of triethylamine, first stir at room temperature for 6 hours; then heat to 50°C, stir for 2 hours, stop the reaction, cool the reaction solution, precipitate it into a large excess of methanol, wash it repeatedly with methanol, and obtain intermediate product A2, vacuum dry it to obtain a white powder for standby use.

[0073] 19.80 g (20 mmol) of intermediate product A2 was added to a three-necked flask that was dried and purged with nitrogen, and 109 ml of solvent N-methylpyrrolidone was added. After complete dissolution, another dianhydride 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic anhydride was gradually added in batches. The mixture was stirred for 12 hours under ice bath. After returning to room temperature, the viscosity was observed. When the viscosity reached 54560 mPa·s, the addition of 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic anhydride was stopped. Tetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic anhydride, at this time, the amount of dianhydride added is 5.70g (19mmol), followed by adding 0.164g (1.0mmol) of end-capping agent 5-norbornene-2,3-dianhydride, stirring at room temperature for 6 hours, then adding a mixture of 8.16g (80mmol) of acetic anhydride and 8.08g (80mmol) of triethylamine, stirring at room temperature for 12 hours, and then heating to 50°C for 2 hours. After the reaction is terminated, the viscous reaction liquid is precipitated into a large amount of methanol, repeatedly washed, and vacuum dried to obtain a transparent polyimide No. 3 sample, which is dissolved and scraped into a 25μm thick film for standby testing.

[0074] Embodiment 4:

[0075] In a dry three-necked flask vented with nitrogen, add 3.2 g (10 mmol) of diamine 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, then add 60 ml of N,N-dimethylacetamide solvent, after complete dissolution, add 0.99 g (5 mmol) of butane-1,2,3,4-tetracarboxylic dianhydride, stir in an ice bath for 10 hours, then warm to room temperature, gradually add dropwise a mixture of 2.04 g (20 mmol) of acetic anhydride and 2.02 g (20 mmol) of triethylamine, first stir at room temperature for 4 hours; then heat to 50°C, stir for 2 hours, stop the reaction, cool down, precipitate the reaction solution into a large excess of methanol, wash repeatedly with methanol to obtain intermediate product A1, vacuum dry to obtain a white powder for standby use.

[0076] 12.57 g (15 mmol) of the intermediate product A1 was added to a three-necked flask that was dried and purged with nitrogen, and 82 ml of the solvent N-methylpyrrolidone was added. After the mixture was completely dissolved, another dianhydride 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic anhydride was gradually added in batches. The mixture was stirred for 10 hours under an ice bath. After the mixture returned to room temperature, the viscosity was observed. When the viscosity reached 55670 mPa·s, the addition of 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic anhydride was stopped. -yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic anhydride, at this time, the amount of dianhydride added is 4.47g (14.9mmol), followed by 0.0356g (0.2mmol) of end-capping agent bicyclo[2.2.2]oct-5-ene-2,3-dicarboxylic anhydride, stirring at room temperature for 4 hours, then adding a mixture of 6.12g (60mmol) of acetic anhydride and 6.06g (60mmol) of triethylamine, stirring at room temperature for 8 hours, and then heating to 50°C for 2 hours. After the reaction is terminated, the viscous reaction liquid is precipitated into a large amount of methanol, repeatedly washed, and vacuum dried to obtain a transparent polyimide No. 4 sample, which is dissolved and scraped into a 25μm thick film for standby testing.

[0077] Comparative Example 1: In a dry three-necked flask vented with nitrogen, 3.2 g (10 mmol) of diamine 2,2'-bis (trifluoromethyl) -4,4'- diaminobiphenyl was added, and then 35 ml of N-methylpyrrolidone solvent was added. After complete dissolution, 4.44 g (10 mmol) of 4,4'- (hexafluoroisopropylene) diphthalic anhydride was added. After stirring in an ice bath for 10 hours, the mixture was warmed to room temperature and gradually dripped with a mixture of 4.08 g (40 mmol) of acetic anhydride and 4.04 g (40 mmol) of triethylamine. The mixture was first stirred at room temperature for 4 hours; then heated to 50 ° C, stirred for 2 hours, the reaction was stopped, and the reaction solution was precipitated into a large excess of methanol after cooling. It was repeatedly washed with methanol to obtain a comparative sample 1, which was dissolved and scraped into a film with a thickness of 25 μm for standby testing.

[0078] Comparative Example 2: In a dry three-necked flask filled with nitrogen, 3.2 g (10 mmol) of diamine 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl was added, and then 35 ml of N,N-dimethylacetamide solvent was added. After complete dissolution, 2.24 g (10 mmol) of hydrogenated pyromellitic anhydride (unresolved isomers) was added. After stirring in an ice bath for 10 hours, the mixture was warmed to room temperature and gradually dripped with a mixture of 4.08 g (40 mmol) of acetic anhydride and 4.04 g (40 mmol) of triethylamine. The mixture was first stirred at room temperature for 4 hours; then heated to 50°C, stirred for 2 hours, the reaction was stopped, and the reaction solution was precipitated into excess methanol after cooling. The mixture was repeatedly washed with methanol to obtain comparative sample 2, which was dissolved and scraped to form a film with a thickness of 25 μm for standby testing.

[0079] Performance evaluation:

[0080] Test Method :

[0081] 1. Infrared spectroscopy (FT-IR), Perkin-Elmer Paragon 1000 Fourier transform infrared spectrophotometer, using KBr pellet method or thin film method for sample preparation;

[0082] 2. Transmittance (%): 25 μm film, UV-1601 SHIMADZU UV-visible spectrometer, measuring the transmittance at 450 nm;

[0083] 3. Stress-strain curve: Instron 5980 tensile testing machine, room temperature, specimen length 100 mm, width 10 mm, tensile rate 2 mm / min;

[0084] 4. TMA test: Mettler-Toledo TMA1 thermomechanical analyzer, 30℃-500℃, heating rate 10℃ / min;

[0085] 5. Thermal gravimetric analysis (TGA): under nitrogen atmosphere, Mettler-Toledo TGA1 thermogravimetric analyzer, 30°C-800°C, heating rate 10°C / min.

[0086] Test Results :

[0087] The test results of transmittance, Tg, thermal decomposition temperature, CTE, tensile strength and elongation at break of the transparent polyimide samples in Examples 1-4 and Comparative Examples 1 and 2 are shown in Table 1 below.

[0088] Table 1: Summary of comprehensive properties of transparent polyimide in Examples 1-4

[0089]

[0090]

[0091] As shown in the table above, the polyimide films of Examples 1-4 of the present invention have high transparency, good heat resistance and low thermal expansion coefficient compared to the comparative examples; while the comparative examples 1 and 2 have high thermal expansion coefficients and their heat resistance is not as good as the films of the present invention.

[0092] The above description is only an example of the implementation of the present invention and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention are included in the protection scope of the present invention.

Claims

1. A transparent polyimide, the main chain structure of which is shown in the following formula (I): in, N is an integer between 15 and 200; Each R1 is independently selected from any one of the following structures: Each R2 is independently selected from a group formed by a capping agent, and the capping agent is selected from a monoanhydride containing an unsaturated bond.

2. The transparent polyimide according to claim 1, wherein the end-capping agent is selected from one or more of the following:

3. The method for preparing the transparent polyimide according to claim 1 or 2, characterized in that: The following steps are involved:

1. A polyamic acid intermediate A is obtained by polymerizing a first dianhydride and a fluorinated diamine, wherein the amount of the first dianhydride used is half the molar amount of the fluorinated diamine; 2. Polymerize the polyamic acid intermediate A and the second dianhydride, add a capping agent to react and obtain polyimide; 3. Precipitating, washing and drying the polyimide to obtain the transparent polyimide; wherein the first dianhydride is butane-1,2,3,4-tetracarboxylic dianhydride and the second dianhydride is 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic anhydride; Wherein, the fluorinated diamine is selected from:

4. The preparation method according to claim 3, wherein the end-capping agent is a monoanhydride containing an unsaturated bond, which is one or more end-capping agents in the following group:

5. A transparent polyimide film, wherein: The film comprises the transparent polyimide according to claim 1 or 2.

6. The polyimide film according to claim 5, having one or more of the following characteristics: a) the transmittance of the transparent polyimide film at a wavelength of 400 nm is above 80%; b) the transparent polyimide film has a thickness between 10 μm and 200 μm; or c) The thermal expansion coefficient of the transparent polyimide film is below 30 ppm / K.

7. The method for preparing the polyimide film according to claim 5 or 6, wherein: The method comprises the steps of dissolving the transparent polyimide according to claim 1 or 2 and coating the resulting film on a carrier.

8. A cover substrate for a flexible display device, comprising the transparent polyimide according to claim 1 or 2, or the transparent polyamide film according to claim 5 or 6.

9. An optical material comprising the transparent polyimide according to claim 1 or 2, or the transparent polyamide film according to claim 5 or 6, or the flexible display device cover substrate according to claim 8.

10. An image display device comprising the transparent polyimide according to claim 1 or 2, or the transparent polyamide film according to claim 5 or 6, or the flexible display device cover substrate according to claim 8, or the optical material according to claim 9.

11. An electronic device or device comprising the transparent polyimide according to claim 1 or 2, or the transparent polyamide film according to claim 5 or 6, or the flexible display device cover substrate according to claim 8, or the image display device according to claim 10.

12. Use of the transparent polyimide according to claim 1 or 2 in preparing a transparent polyimide film or a display device cover substrate.

Citation Information

Patent Citations

  • Colorless transparent polyimide thin film and preparation method thereof

    CN108424540A

  • Polyimide, polyimide solution, and polyimide film

    CN110475806A

  • Colorless transparent polyimide film with stable size and preparation method thereof

    CN111087812A

  • Colorless transparent polyimide film

    CN113366051A

  • Resin precursor and resin composition containing the same, resin film and manufacturing method therefor, and laminate and manufacturing method therefor

    CN111892708A